ACADEMIC EMOTIONS OF LEARNING ENGLISH THROUGH ENGLISH NATIVE SPEAKER’S VIDEOS ON YOUTUBE: STUDENTS’ VOICE - Sarmila, Sarmila; Rachmawati, Andi; Muflihun, Muflihun (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Academic emotions are the feelings or emotions that students experience when they are learning. This study aimed to analyze students' academic emotions regarding the use of English-native speaker videos on YouTube for learning vocabulary. A qualitative design was used to conduct the study, which employed a questionnaire and in-depth interviews to collect data. The participants of this study were third- and fifth-semester English major students at Universitas Muhammadiyah Kendari. The findings showed that, in terms of positive emotions, students enjoyed the learning process and were motivated to continue learning vocabulary. It was because the videos of English native speakers on YouTube provided interesting material, easy-to-understand pronunciation, and freedom to choose topics. Students were optimistic about the benefits of these videos for vocabulary improvement and proud of their learning achievements when learning vocabulary. Furthermore, in the negative emotions, it showed that the students did not feel desperate when learning vocabulary through native speaker videos on YouTube, and students generally do not get bored because they can overcome boredom in various ways, such as choosing short videos, changing to other videos, or taking short breaks. These conclusions suggest that English-native speaker videos on YouTube are an effective and enjoyable vocabulary learning medium for students.